2019
DOI: 10.1108/ijchm-09-2018-0742
|View full text |Cite
|
Sign up to set email alerts
|

Green hotel adoption: a personal choice or social pressure?

Abstract: Purpose This study aims to examine the potential guest perception of green hotel attributes (GHAs) and the underlying mechanism through which GHA perception influences attitude toward green hotels, intention to stay at green hotels and willingness to pay a premium. It also investigates the moderating roles of personal norms and social norms in the influence of GHA perception on identification and trust toward green hotels. Design/methodology/approach A two-stage survey was used to collect data via Prolific A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 46 publications
5
79
0
4
Order By: Relevance
“…In this sense, firstly, the results obtained demonstrated: a) the existence of a positive and direct bond between the ecological measures developed by hotels and their image, as reported previously by other authors (Durna et al, 2015;Mart ınez Garc ıa de Leaniz et al, 2018;Palacios-Florencio et al, 2016Wang et al, 2018); b) that green initiatives positively influence guests' trust; these findings are consistent with previous studies (e.g. Balaji et al, 2019;Palacios-Florencio et al, 2016; c) that, while tourists experience a satisfactory service, the green initiatives developed by the hotels have a positive impact on their satisfaction, thus confirming the results of previous research (Merli et al, 2019;Verma & Chandra, 2016, Wang et al, 2018Yusof et al, 2017).…”
Section: Discussion Implications Limitations and Future Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…In this sense, firstly, the results obtained demonstrated: a) the existence of a positive and direct bond between the ecological measures developed by hotels and their image, as reported previously by other authors (Durna et al, 2015;Mart ınez Garc ıa de Leaniz et al, 2018;Palacios-Florencio et al, 2016Wang et al, 2018); b) that green initiatives positively influence guests' trust; these findings are consistent with previous studies (e.g. Balaji et al, 2019;Palacios-Florencio et al, 2016; c) that, while tourists experience a satisfactory service, the green initiatives developed by the hotels have a positive impact on their satisfaction, thus confirming the results of previous research (Merli et al, 2019;Verma & Chandra, 2016, Wang et al, 2018Yusof et al, 2017).…”
Section: Discussion Implications Limitations and Future Researchsupporting
confidence: 91%
“…In this sense, trust in the environmental measures implemented by eco-friendly hotels is critical, given that consumers may suspect that the reason for green practices could be cost savings for the hotel or improvement of its reputation, rather than any real commitment to the environment (Sukhu & Scharff, 2018). Authors such as Palacios-Florencio et al (2016 and Balaji et al (2019) find empirical support for the positive influence of environmental practices implemented by hotels on the trust of their guests. Accordingly, the following hypothesis was considered: H2: Hotel green practices directly and positively influence the trust of hotel guests.…”
Section: Trustmentioning
confidence: 99%
“…That is in accordance with almost all previous researches that implement SEM in general. Moderation analysis is rarely present [20,36] or fails to provide significant differences in those researches [20]. However, when moderation analysis is performed within this research, based on the phase in behavior change (pre-decision, pre-action, action), it can be concluded that the significant influence of all the variables is not present in each of the phases.…”
Section: Discussionmentioning
confidence: 75%
“…A research conducted in the UK [36] considers the elements of TPB within the stimulus-organism-response framework, together with elements of the norm-activation theory, and social identity theory. Hereby, the authors consider the influence of green hotel attributes (presented as a higher-order formative construct consisting of five reflective first-order dimensions: customer benefit, energy efficiency, recycling policy, water efficiency, and green landscape) through personal route and social route.…”
Section: Literature Reviewmentioning
confidence: 99%
“…and their effects on the environment. An increasing number of hotels are engaging in sustainable hotel operations to address environmental issues, and consequently, obtain a differential competitive advantage [12,13].…”
Section: Sustainability and Hotelsmentioning
confidence: 99%